Coordination beyond the state to solve complex water problems: Insights from South Africa - Sabine Stuart-Hill; Evelyn Lukat; Catherine Pringle; Claudia Pahl-Wostl (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
This Briefing Paper presents one of six analyses of cross-sectoral coordination challenges that were conducted as part of the STEER research project and on which separate Briefing Papers are available. South Africa's water legislation is internationally recognised for its ambitious implementation of integrated water resource management (IWRM). IWRM is a concept that was developed to address complex water challenges by considering the connections between land and water, and widening the knowledge space to other water-using sectors and actors. Stakeholder participation and coordination - key aspects to IWRM - represent a network governance style, which contrasts with the hierarchical governance style that most governments embody. We find three challenges regarding the implementation of IWRM in South Africa: Firstly, a dual governance system: The landscape of South African organisations relevant to catchment management consists of organisations from the western administrative and traditional governance systems. The western administrative governance system includes organisations such as the Department of Water and Sanitation (DWS), which is mandated to manage water resources, and the Department of Cooperative Governance and Traditional Affairs, which mediates with traditional authorities regarding various issues, including land management. Currently, these organisations do not cooperate on land-water issues as needed. Secondly, a lacking implementation of water legislation: The South African National Water Act of 1998 outlines Catchment Management Agencies (CMA) as network governance structures that should manage the catchment at a local scale and include all water users. However, after more than 20 years, these structures have not been implemented. This is also due to a conflict in governance styles between the stakeholder-integrating CMAs and the expert-driven, hierarchical DWS. Thirdly, conflict between governance styles: In the absence of the CMA, several informal or non-statutory network governance structures have developed in the uMngeni catchment (e.g. Catchment Management Forums and the uMngeni Ecological Infrastructure Partnership). In several instances, actors representing these structures and government representatives are in conflict over the different approaches to knowledge management and decision-making; these differences are rooted in their respective governance styles. In the last few years, the DWS started the process of a Catchment Management Strategy, which requires stakeholders to participate and formulate their needs. This process could become a mediating tool for the conflicts that arise between the actors when using the different hierarchical and network governance styles. We propose the following recommendations: 1. Integrating traditional authorities into planning processes in a culturally sensitive way is crucial in supporting IWRM. 2. Network structures - designed by government or self-organised - may provide the social capital needed at the local and regional governance levels to implement IWRM. 3. In order to mediate between the existing hierarchical and network governance knowledge, management strategies should represent a hybrid governance style.
Keywords: 330